Phytochemical contents and antioxidant activities of fern, Asplenium ceterach L. in different altitudes (Bangladesh Journal of Botany, 2019)
Phytochemical contents and antioxidant activities of fern (Asplenium ceterach L.) distributed in different altitudes (22 stations) were compared and the relationships between altitude and plant chemical contents were studied. The highest 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity was found in 22nd station (IC50 = 47.91 μg/ml) and the highest total phenolic content was found in 9th station (110.62 μgGAE/ml) whereas the maximum total flavonoid content was found in 20th station (232.67 μgCE/ml). High performance liquid chromatography (HPLC) analysis indicates that the maximum pterosin b (0.235 μg/ml), catechin (2.756 μg/ml) and quercetin (0.207 μg/ml) values were found in 21th station whereas the maximum chlorogenic acid (17.718 μg/ml) was obtained in 9th and caffeic acid (6,598 μg/ml) in 13th stations. It was observed that altitude is not potent alone, but it can be a factor in the occurrence of other ecological factors like soil properties, water, humidity, light and temperature.